Pengaruh Kegiatan-Kegiatan Agama Islam Terhadap Penguatan Pendidikan Karakter Sikap Religius Siswa di SMP Khadijah Surabaya - Rohim, Baitur (Universitas Negeri Surabaya, 2022)
Character education efforts at Khadijah Middle School to continue to make Islamic religious activities an indispensable activity are so that the students' personal character has Islamic principles and values. strengthening Islamic activities is an implementation of the values of Islamic religious education, in which the physical and spiritual needs of students are needed. This research uses quantitative methods. The population in this study were all 155 grade 8 students at SMP Khadijah Surabaya, with data collection obtained through a questionnaire. The results of this study show that the results of the simple regression test and the Fcount regression test are 339.704 with a significance level of 0.000 <0.05. This shows that the variable Islamic religious activities has a very significant influence on the character education of SMP Khadijah Surabaya students. The results of the hypothesis in this study are that there is a significant influence of Islamic religious activities on students' religious attitudes to strengthen character education so that the hypothesis is accepted. So it can be concluded that there is a significant influence of Islamic religious activities on students' religious attitudes to strengthen student character education at SMP Khadijah Surabaya. This perception has a significant influence of 68.9%. So that it can strengthen the existence of a very strong and large influence.